Rational Design And Synthesis Of Peptide Inhibitors Of Ns2b/Ns3 Protease As Therapeutic Agents For Dengue Virus Type 2 - Abdalrazaq, Nadeem Abdalsatar (2021)
The main objectives of this study are to design potent and selective peptide inhibitors by studying the interactions between the designed peptides and the NS2B/NS3 dengue protease using two independent docking programs (MOE and AutoDock4.2), thus, to evaluate the quantitative and qualitative docking results from both programs. The other objectives are to synthesize and characterize the potential peptides by using Fmoc Solid Phase Peptide Synthesis (SPPS) technique, to perform NS2B/NS3 dengue protease expression and purification, and finally to investigate the biological evaluation of the selected peptides using in vitro NS2B/NS3 dengue protease inhibition assay.